Pengaruh Sistem Informasi Akuntasi dan Human Capital Terhadap Pengelolaan Pada UMKM - Tanjung, Fachreza Rahmad; Husna, Asmaul (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the role of Accounting Information Systems and Human Capital in Financial Management in Micro, Small, and Medium Enterprises (MSMEs). The research method used is qualitative with a literature review analysis technique. The literature review conducted in this study is a form of research carried out by collecting journal articles with themes aligned with the research objectives, namely the challenges faced by MSMEs in achieving their goals from an economic perspective. This study utilized the Publish or Perish software to gather relevant journal articles and subsequently conducted content analysis. The results show that the Accounting Information System has a significant positive effect on financial management, and Human Capital also has a significant impact on improving the quality of financial management. These findings indicate that the integration of technology and human resource development is crucial in optimizing financial management in MSMEs. This research contributes to the development of financial management strategies for MSMEs, especially in adapting to digital transformation.